2018
DOI: 10.1038/s41598-017-19022-1
|View full text |Cite
|
Sign up to set email alerts
|

The space charge limited current and huge linear magnetoresistance in silicon

Abstract: Huge magnetoresistance in space charge regime attracts broad interest on non-equilibrium carrier transport under high electric field. However, the accurate fitting for the current-voltage curves from Ohmic to space charge regime under magnetic fields has not been achieved quantitatively. We conjecture that the localized intensive charge dynamic should be taken into consideration. Here, by introducing a field-dependent dielectric constant, for the first time, we successfully simulate the current-voltage curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…The discrepancy may be attributed to the distribution of dopants along the surface and the energy level of dopants in the band gap. Our previous work showed that a large magnetoresistance and the successive Ohmic and MG regimes could be observed in a current perpendicular to plane (CPP) configuration [6], which can be well simulated by a model proposed by Zhang and Pantelides [2]. In fact, it has been predicted in theory that an ETF regime could be "stretched" to different voltage ranges by the concentration of dopants [1].…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…The discrepancy may be attributed to the distribution of dopants along the surface and the energy level of dopants in the band gap. Our previous work showed that a large magnetoresistance and the successive Ohmic and MG regimes could be observed in a current perpendicular to plane (CPP) configuration [6], which can be well simulated by a model proposed by Zhang and Pantelides [2]. In fact, it has been predicted in theory that an ETF regime could be "stretched" to different voltage ranges by the concentration of dopants [1].…”
Section: Resultsmentioning
confidence: 82%
“…When all available states in the band gap are filled with carriers, the I-V curve rises up and conforms to the square law (I∝V 2 ). Hence, another critical voltage V U for the ETF regime is defined [1][2][3][4][5][6], and the MG regime can be identified. Two critical voltages, V L and V U , are the lower and upper limitations of the ETF regime.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations